(3JMaI GdCRgGQ hRdGd GdCfgGQ aj fSH GdCFeI hGdCWgGQs - (3VGef Hf TObe Hf Ydj Hf MSf Hf GdfbjH GdeOfj GdMeRj GdMSjfj, GHf TObe,J (B1088 (3g` s
(3ChdgG (B:s
(3gPG LdO GdKGdK (B](3cPG(B] (3ef JMaI GdCRgGQ hCfg PcQ ai CehGdg CMhGd eMeO GdHGbQ Ydjg GdSdGe haVGFdg s
(3BNQgG (B:s
(3Ke PcQ MOjK McjeI HfJ eMeO GdLhGO HJeGeI , hPcQ GdENJdGa ai hdGOJg ai GdTghQ hGdSfI GfJgi s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B213s
(3GdPQjYI (B- (3GdLRA (B3 - (3U (B419 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B94 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs